TaleSpin. Volume 3 [videorecording (DVD)] (Disney DVD., 2013)
Beloved Jungle book star Baloo the bear and his navigator Kit Cloudkicker take to the skies as couriers for their friend and boss, the always resourceful businesswoman Rebecca Cunningham. With Rebecca's adventurous daughter Molly and ace mechanic Wildcat rounding out the crew, the Higher for Hire crew is joined by the most memorable cast of colorful characters and scheming villains yet.